PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III.C SDN 020 JAYA MUKTI TAHUN PELAJARAN 2013/2014 - Sofyan Amri Sofyan Amri; Hendri Marhadi Hendri Marhadi; Gustimal Witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. His research is motivated by low yields III.C grade social studies students Jayamukti Elementary School 020. Based on the results of the initial observations of the number of students who completed the pre cycle amounted to only 10 people, or 26%. The low yield is due to a lack of learning activities of students in learning and lack of interest of students towards learning as a method of teaching social studies teacher monotonous. To overcome this, the researchers conducted a study to apply the learning model CTL (Contekstual Teaching Learning) in social studies learning. This research is a form of action research conducted with the cycles of nature are two phases of planning, implementation, observation and reflection. The subjects were III.C grade students of SD Negeri Jayamukti 020. Data collection techniques are performed through testing and observation techniques using descriptive data analysis techniques. From the results of the first cycle of students who pass higher than during the pre-cycle was 23 people or 61% and the second cycle was also an increase amounted to 36 people or 95%. So it can be concluded that by using a learning model CTL (Contekstual Teaching Learning) to improve learning outcomes IPS III.C grade Elementary School Students 020 Jayamukti. Keyword. Contectual teaching and learning, outcome learning IPS